Induction of TLR4/TLR2 Interaction and Heterodimer Formation by Low Endotoxic Atypical LPS - Francisco, Sara; Billod, Jean-Marc; Merino, Javier; Punzón, Carmen; Gallego, Alicia; Arranz, Alicia; Martin-Santamaria, Sonsoles; Fresno, Manuel (Frontiers in Immunology, 2022)
The toll-like receptor 4 (TLR4)/myeloid differentiation protein-2 (MD-2) complex is considered the major receptor of the innate immune system to recognize lipopolysaccharides (LPS). However, some atypical LPSs with different lipid A and core saccharide moieties structures and compositions than the well-studied enterobacterial LPSs, can induce a TLR2-dependent response in innate immune cells. Ochrobactrum intermedium, an opportunistic pathogen, presents an atypical LPS. In this study, we found that O. intermedium LPS exhibits a weak inflammatory activity compared to E. coli LPS, and more importantly is a specific TLR4/TLR2 agonist, able to signal through both receptors. Molecular docking analysis of O. intermedium LPS predicts a favorable formation of a TLR2/TLR4/MD-2 heterodimer complex, which was experimentally confirmed by FRET in cells. Interestingly, the core saccharide plays an important role in this interaction. This study reveals for the first time TLR4/TLR2 heterodimerization that is induced by atypical LPS and may help to escape from recognition by the innate immune system.